Retrospective Comparison of Postoperative Fascia Iliaca Block and Multimodal Drug Injection on Early Function of the Knee in Femoral Fractures Using Retrograde Intramedullary Nailing - Songtao Li; Ping Luo; Yuhu Huang; Huarong Xia; Wushu Wei; Wendun Wei; Tianyu Xia; Kai Xu (Pain Research and Management)
Introduction. There is a common concern about the pain and rehabilitation of the knee after femoral retrograde intramedullary nailing. It is essential for early postoperative knee function required for physical self-maintenance in daily life. And a favorable rehabilitation of the knee usually promotes the quality of life. However, early rehabilitation is absent or insufficient for many patients in postoperative management. This retrospective study aims to evaluate the effect of early knee function improvement in comparison to postoperative fascia iliaca blocking (FIB) and multimodal drug injection (MDI). Patients and Methods. A retrospective analysis of 41 patients receiving femoral fracture treatment with retrograde intramedullary nailing, was performed during 2018–2020. 19 patients were treated with MDI as postoperative analgesia, and 22 patients were treated with FIB. Rehabilitation started on the first postoperative day and lasted for 3 months. Visual analog scale (VAS), the range of motion (ROM) of the knee, and single assessment numeric evaluation (SANE) were assessed. Results. There was no significant difference shown in any of the demographic, fracture types, and operative time. All patients performed regular and voluntary knee rehabilitation and weight-bearing at home following the instruction from the orthopedic staff. Pain in the FIB group at postoperative 1-day was milder (1.7 ± 1.1), compared with that in the MDI group (2.8 ± 1.3, p=0.038). There was a significant difference in VAS between two groups at postoperative 1-month (p=0.031), with a peak score in the FIB group (3.3 ± 0.9). At postoperative 3-month, both groups had pain relief with similar VAS (p=0.465). The ROM of the knee in both groups was continuously improved during the first three months. The SANE in the MDI group was significantly different compared with FIB at 1-month (p=0.026). However, scores of SANE were similar in both groups at 3 months (p=0.541). All patients were identified as fractures union at 9-month or 12-month follow-up. Conclusion. The knee pain was commonly experienced in this series of retrograde femoral nailings. Both MDI and FIB provided immediate and effective pain control after femoral fracture surgery. MDI was more beneficial to continuous pain control and knee rehabilitation in the early follow-up. The extent of pain relief and knee function improvement reached the same level at postoperative 3-month.